Government Policy on Jatijajar Cave as a Community Economic Empowerment through Participation in Bapak Village, Jatijajar Subdistrict, Kebumen Regency - Erich Fitiawan; N Nasiwan (CV. Media Digital Publikasi Indonesia, 2023)
Economic problems and the welfare of the community are quite high, encouraging the government to continue to explore the potential of natural resources and human resources owned by a region, then develop it to support the economy and welfare of the community, one of which is in the field of tourism. For tourists and the community to know and be able to enjoy a tourist attraction, it is necessary to make efforts to manage tourist attractions. The focus of the study in this research is focused on the preposition: 1) The implementation of local government policies related to tourism must be supported by community empowerment in the development of micro-enterprises so that it will have an impact on improving the local economy; 2) Sustainable empowerment will be able to reduce the level of structural unemployment; 3) The higher the community participation in managing tourism objects, the more positive socio-economic changes will occur in the community. The purpose of this study is to analyze the relationship between community participation and empowerment as well as public policy in managing tourist attractions in Kebumen Regency and its impact on the economy